2004
DOI: 10.1111/j.1749-7345.2004.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Supplementation of Pond Waters for Inland Culture of Marine Shrimp

Abstract: Saline well water used to fill ponds for inland culture of marine shrimp in Alabama often have low concentrations of potassium and magnesium. In 2002, pond waters on a shrimp farm were treated with enough muriate of potash and potassium‐magnesium sulfate (K‐Mag) to increase potassium concentration from 6.2 mg/L to about 40 mg/L and magnesium concentrations from 4.6 mg/L to about 20 mg/L. Salinity in ponds averaged 2.6 ppt at the time of mineral salt additions. The concentrations of potassium and magnesium rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
83
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 6 publications
3
83
0
1
Order By: Relevance
“…Farmers in the West Alabama have been successful in raising L. vannamei in IGSW by raising the K + and Mg 2+ levels of their pond waters to correct ionic ratio imbalances (McNevin et al, 2004). In India, the culture of L. vennamei was successfully demonstrated and commercialized in K + and Mg 2+ fortified IGSW by Lakra et al, (2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farmers in the West Alabama have been successful in raising L. vannamei in IGSW by raising the K + and Mg 2+ levels of their pond waters to correct ionic ratio imbalances (McNevin et al, 2004). In India, the culture of L. vennamei was successfully demonstrated and commercialized in K + and Mg 2+ fortified IGSW by Lakra et al, (2014).…”
Section: Introductionmentioning
confidence: 99%
“…These strategies include feed modification, offered to shrimp, usually with supplements that might theoretically improve osmo-regulatory capacity . Second strategy is the culture of marine shrimp in pond system with ionic supplementation in water (McNevin et al, 2004). It is reported that the use of fertilizers for the ionic fortification in inland saline aquaculture water could be costly.…”
Section: Introductionmentioning
confidence: 99%
“…Inland shrimp farming in low-salinity well waters (LSWW) is a growing industry in the United States and various other countries around the world (Boyd and Thunjai 2003;Saoud et al 2003;McNevin et al 2004). Inland aquaculture of marine species is desirable for many reasons, notably biosecurity, reduced property prices, and availability of saline waters that are unsuitable for traditional agriculture (Hopkins et al 1996).…”
mentioning
confidence: 99%
“…However, previous research showed that inland well waters were generally very low in salinity and had ionic compositions that were significantly different from those of seawater (Boyd and Thunjai 2003;Saoud et al 2003). Moreover, potassium (K þ ) was deficient in the majority of these waters (Saoud et al 2003;McGraw and Scarpa 2003;McNevin et al 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation